De-stress your physiological activation by compressing your imagination: a brief session of hypnosis decreases sympathetic stress response in moderately stressed dentists - Queirolo, Luca; Facco, Enrico; Roccon, Andrea; Pistollato, Elisa; Di Fiore, Adolfo; Fazia, Teresa; Bacci, Christian; Zanette, Gastone (Frontiers in Psychology, 2025)
AimThis study aims to explore the effect of hypnosis on dentists’ physiological stress management.MethodsThe study included 20 dentists (mean = 30, SD = 7.37) from the Dental Clinic of the University of Padua. Stress assessment was performed by recording several physiological parameters, including heart rate (HR), heart rate variability (HRV), electrodermal activity (EDA), skin conductance responses (SCRs), and the administration of the psychological stress perceived stress scale (PSS-10). Following hypnosis induction, participants were led to recall and relive a previously agreed-upon, pleasant experience, while the related psycho-physiological changes were monitored. The hypnosis session was planned on a regular working day. Physiological parameters were recorded using the Empatica E4 wristband and eSense galvanometer. Measurements were taken at baseline, during hypnosis, and after dehypnotization.ResultsParticipants exhibited moderate stress levels before hypnosis (mean PSS-10 = 17.1 ± 8.1). After hypnosis, a significant and large decrease in SCRs (T-test = 3.24, DF = 19, p = 0.002, as shown also by Cohen’s d = 0.724) and an increase in EDA (Wilcoxon = 50, DF = 18, p = 0.00355) were recorded, while HRV did not show significant changes. Friedman ANOVA for repeated measures models, and Nemenyi post-hoc correction indicated that the condition (basal, hypnosis, and post-hypnosis) significantly affected SCR levels (p = 0.00008), especially in the pre vs. post (p = 0.012313) and in the hypnosis vs. post comparisons (p = 0.00005819). Friedman ANOVA for repeated measures models and Durbin–Conover indicated that conditions (basal, hypnosis, or post-hypnosis) also influenced EDA levels, while HRV did not show any significant change (tested with ANOVA repeated measures). Pearson’s correlation showed that PSS-10 levels were inversely correlated with SCRs in hypnosis (p = 0.019, DF = 18, R = −0.51). A linear regression model fitting delta SCRs (post-pre physiological activation) showed that SCR-pre explained part of the outcome (R = 0.647, R^2 adj = 0.386, AIC = 99.6, F = 13, RMSE = 2.51, p = 0.002). Regarding subjective perception, 18/20 participants reported feeling better, 2 reported no difference χ2 = 29.2, p = 0.00000047, df = 2. Furthermore, the Bayesian paired samples T-test comparing SCR-pre vs. post showed a BF+₀ = 20.7, error % = 0.000824, which strongly indicates the superiority of the effectiveness of training in comparison to null hypotheses (>20 times probable than an effect than no effect).ConclusionOur data suggest that hypnosis could be a valuable resource for stressed dentists. Longitudinal controlled studies and larger samples are necessary to corroborate our results and to check the durability of effects over time. Anyway, our results suggests that a short session of hypnosis (or perhaps, self-hypnosis) during a regular working day may help relieve the sympathetic stress response.